The CODESRIA debate on academic and intellectual freedom in Africa: the role and responsibility of African intellectuals - Cabe, Loyiso (Rhodes University, Faculty of Humanities, Department of Political and International Studies)
According to Fagunwa (2011), intellectuals serve as the glue that binds societies together and serve as the foundation upon which new civilizations are created and dismantled. The Council for the Development of Social Science Research in Africa (CODESRIA) of 1990 entrusted intellectuals with crucial transformative tasks (roles) and responsibilities in Africa. This study explores the transformational roles and responsibilities of African intellectuals in neo-liberal and neo-colonial Africa as well as how academic freedom must be understood by African academics in accordance with the present debate on academic freedom in South Africa, which was fueled by Nattrass (2020) paper. The primary premise of this study is that academic freedom in Africa today is viewed differently than it was during the CODESRIA meeting on academic freedom in 1990, and that this is because of African intellectuals not carrying out their roles and responsibilities in Africa. In CODESRIA 1990, academic freedom referred to an academic's unrestricted, yet responsible, right to pursue their academic interests (CODESRIA 1990; Kampala Declaration 1990). African academics now understand academic freedom to be merely their own freedom, unrelated to their responsibility to use it ethically and professionally. Hence, for them, academic freedom entails the freedom to express oneself without restrictions or fear of criticism (Chachage, 2008; Nattrass, 2020b; Esso, and Long, 2020). Looking at this current misinterpretation of academic freedom, the 1990 CODESRIA meeting is a good reference point to the debate on academic freedom in Africa and role and responsibility of African intellectuals. This is because, it was where academic freedom and the role and responsibility of African intellectuals in Africa was professionally conceptualized. Thus, this study reviews the 1990 CODESRIA debate to understand the role and responsibility of African intellectuals. This study utilizes two theories, Social Constructivism Theory and the Social Responsibility Theory, to explain the position it has taken on the subject at hand. Thus, these theories provide an umbrella and a point of departure for understanding the context and dynamics of the ongoing conflict between academic freedom and social responsibility in South Africa's higher education institutions.
Keywords: Codesria; Academic freedom; Social responsibility; Neoliberalism; Pan-Africanism; Colonization; Decolonization; Neocolonialism; Intellectuals Africa